2010
DOI: 10.1002/cctc.200900288
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Lipase Adsorption on SBA‐15: Effect of Different Interactions on Enzyme Loading and Catalytic Performance

Abstract: Immobilization of Pseudomonas fluorescens lipase (Pfl) on the chemically modified, or unmodified, surface of SBA‐15 mesoporous silica has been achieved. X‐ray diffraction (XRD), transmission electron microscopy (TEM), and N2 physisorption are used to monitor the effect of surface functionalization on the structural and textural features of the SBA‐15 silica support. The enzyme loading strongly depends on the type of enzyme–support interaction, the maximal loading of the chemisorbed lipase being about twice tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 43 publications
0
56
0
Order By: Relevance
“…Silicas of different dispersive-morphological parameters and porous structures have been proposed. A representative silica used for the enzyme immobilization on a large scale is mesoporous silica SBA-15 (Santa Barbara Amorphous) with hexagonal array of pores (Salis et al 2010;Thorn et al 2011). It is characterized by small pores, from 5 to about 30 nm in diameter and a hexagonal array of pores (Grudzień et al, 2006;2007;Hartmann and Kostrov 2013).…”
Section: Inorganic Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicas of different dispersive-morphological parameters and porous structures have been proposed. A representative silica used for the enzyme immobilization on a large scale is mesoporous silica SBA-15 (Santa Barbara Amorphous) with hexagonal array of pores (Salis et al 2010;Thorn et al 2011). It is characterized by small pores, from 5 to about 30 nm in diameter and a hexagonal array of pores (Grudzień et al, 2006;2007;Hartmann and Kostrov 2013).…”
Section: Inorganic Carriersmentioning
confidence: 99%
“…Lipases catalyse the hydrolysis of esters formed by short-and long-chain alcohols, mono-and multi-hydroxides, and saturated and unsaturated carboxylic acids of short and long chains. The catalysts based on lipases are used in the reactions of esterification or transesterification of different substrates (Brem et al 2011;Liu et al 2013;Yu and Fang 2013), and in the process of biodiesel production (Salis et al 2010;Mendes et al 2011;Tran et al 2012). A wide use of this group of proteins and their affinity to many carriers permit their immobilization on many organic and inorganic carriers.…”
Section: Immobilized Enzymesmentioning
confidence: 99%
“…Therefore intense research efforts to use OMS as carriers for enzymes and therapeutic proteins to obtain either stable biocatalysts or efficient drug delivery systems are expanding [13][14][15][16][17][18]. For example we found that the biocatalysts obtained using Pseudomonas Page 6 of 39 A c c e p t e d M a n u s c r i p t 5 fluorescens lipase adsorbed on mesoporous silica (SBA-15 and MSE) have a very good performance in terms of transesterification activity and recycling towards sunflower oil for the production of biodiesel [19,20]. On the other hand, silica based ordered mesoporous materials can also be considered for the physical adsorption of therapeutic biomolecules as a consequence of the relatively good biocompatibility of silica materials [21].…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, a covalently attached therapeutic protein will not be easily released from the support. On the contrary, chemical binding may be an important option for biocatalysis since covalently attached enzymes are usually more stable than those physically adsorbed [20] Remarkably, during the covalent binding a structural distortion of the enzyme may occur with the partial loss of the biological activity. This is the reason why physical adsorption is also important in biocatalytic purposes (only a minimal loss of enzyme activity generally occurs), and becomes particularly competitive for the use of immobilized enzymes in non conventional (organic) media [46,47].…”
Section: Introductionmentioning
confidence: 97%
“…The lipase from Pseudomonas fluorescens is a very interesting heat-resistant biocatalyst that is currently employed in many esterification and transesterification reactions [8]. The methods already used for the immobilization of Pseudomonas fluorescens lipase include physical adsorption [9], chemical adsorption [10], entrapment [11], sol-gel encapsulation [12] and covalent attachment [13]. Although the activity of covalently-immobilized enzymes is generally lower than the activity of the soluble enzymes, it was for instance reported that covalent immobilization onto Eupergit C resulted in a higher activity than the activity of soluble enzymes [14].…”
Section: Introductionmentioning
confidence: 99%